Automatic delineation of debris-covered glaciers using InSAR coherence derived from X-, C- and L-band radar data: a case study of Yazgyl Glacier - Lippl, Stefan; Vijay, Saurabh; Braun, Matthias (Journal of Glaciology, 2018)
Despite their importance for mass-balance estimates and the progress in techniques based on optical and thermal satellite imagery, the mapping of debris-covered glacier boundaries remains a challenging task. Manual corrections hamper regular updates. In this study, we present an automatic approach to delineate glacier outlines using interferometrically derived synthetic aperture radar (InSAR) coherence, slope and morphological operations. InSAR coherence detects the temporally decorrelated surface (e.g. glacial extent) irrespective of its surface type and separates it from the highly coherent surrounding areas. We tested the impact of different processing settings, for example resolution, coherence window size and topographic phase removal, on the quality of the generated outlines. We found minor influence of the topographic phase, but a combination of strong multi-looking during interferogram generation and additional averaging during coherence estimation strongly deteriorated the coherence at the glacier edges. We analysed the performance of X-, C- and L- band radar data. The C-band Sentinel-1 data outlined the glacier boundary with the least misclassifications and a type II error of 0.47% compared with Global Land Ice Measurements from Space inventory data. Our study shows the potential of the Sentinel-1 mission together with our automatic processing chain to provide regular updates for land-terminating glaciers on a large scal
Keywords: debris-covered glaciers; glacier delineation; glacier mapping; glacier monitoring; remote sensing

Early 21st century spatially detailed elevation changes of Jammu and Kashmir glaciers (Karakoram–Himalaya) - Vijay, Saurabh; Braun, Matthias (Global and Planetary Change, 2018)

Elevation change rates of glaciers in the Lahaul-Spiti (Western Himalaya, India) during 2000-2012 and 2012-2013 - Braun, Matthias; Vijay, Saurabh (Remote Sensing, 2016)
Keywords: Geodetic glacier mass balance; Glacier elevation change; InSAR processing; Lahaul-Spiti; SRTM; TanDEM-X

Seasonal and interannual variability of Columbia Glacier, Alaska (2011-2016): Ice Velocity, Mass Flux, surface elevation and front position - Braun, Matthias; Vijay, Saurabh (Remote Sensing, 2017)
Keywords: Bistatic InSAR; Columbia Glacier; Elevation changes; Mass flux; Offset tracking; Seasonal velocity; TanDEM-X mission